9-[2-(R)-(Phosphonomethoxy)propyl]-2,6-diaminopurine (R)-PMPDAP and its prodrugs: optimized preparation, including identification of by-products formed, and antiviral evaluation in vitro - Krečmerová, Marcela; Jansa, Petr; Dračínský, Martin; Sázelová, Petra; Kašička, Václav; Neyts, Johan; Auwerx, Joeri; Kiss, Eleonóra; Goris, Nesya; Stepan, George; Janeba, Zlatko (Bioorganic & medicinal chemistry, 2013)
New large-scale synthetic approach to antiretroviral agent 9-[2-(R)-(phosphonomethoxy)propyl]-2,6-diaminopurine, (R)-PMPDAP, was developed. Reaction of (R)-propanediol carbonate with 2,6-diaminopurine afforded exclusively (R)-9-(2-hydroxypropyl)-2,6-diaminopurine which was subsequently used for introduction of a phosphonomethyl residue using TsOCH(2)P(O)(OiPr)(2) or BrCH(2)P(O)(OiPr)(2) followed by deprotection of ester groups. All minor ingredients and by-products formed during the process were identified and further studied. The final product was obtained in high yield and its high enantiomeric purity (>99%) was confirmed by chiral capillary electrophoretic analysis using β-cyclodextrin as a chiral selector. Antiretroviral activity data of (R)-PMPDAP and its diverse prodrugs against HIV and FIV were investigated. Akin to (R)-PMPDAP, both prodrugs inhibit FIV replication in a selective manner. Compared to the parent molecule, the amidate prodrug was 10-fold less active against FIV in cell culture, whereas the alkoxyalkyl ester prodrug was 200-fold more potent in inhibiting FIV replication in vitro.
Keywords: Organophosphorus Compounds; Antiviral Agents; Stereoisomerism; Immunodeficiency Virus, Feline; antivirové látky; organofosforové sloučeniny; virus kočičí imunodeficience; HIV-1; Adenine; adenin; prekurzory léčiv; stereoizomerie; Prodrugs